2012
DOI: 10.4236/jmp.2012.310194
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Concentration Distribution of <sup>131</sup>I, <sup>132</sup>I, <sup>133</sup>I, <sup>134</sup>I, and <sup>135</sup>I Due to a Hypothetical Accident of TRIGA Mark-II Research Reactor

Abstract: The present work gives a methodology for assessing radiological concentration of <sup>131</sup>I, <sup>132</sup>I, <sup>133</sup>I, <sup>134</sup>I, and <sup>135</sup>I due to a hypothetical accident of TRIGA Mark-II research Reactor at AERE, Savar, Bangladesh. The concentrations were estimated through different pathways like ingestion of vegetation, milk, and meat from air and ground deposition. The maximum air concentrations for all 16 directions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Hikaru et al [7] conducted a study on the radiological aspects of fallout from the Fukushima Daiichi nuclear power plant accident by measuring radiation in the Chiba metropolitan area from March 15 th , 2011. Malek, et al [8] conducted another study to evaluate the radiological doses resulting from the deposition of Research Article 131 I, 132 I, 133 I, 134 I, and 135 I on the ground, vegetation, milk, and meat in the event of a hypothetical accident involving a TRIGA research reactor. The study found that 131 I contributes the most to the dose in vegetation compared to all other radionuclides.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hikaru et al [7] conducted a study on the radiological aspects of fallout from the Fukushima Daiichi nuclear power plant accident by measuring radiation in the Chiba metropolitan area from March 15 th , 2011. Malek, et al [8] conducted another study to evaluate the radiological doses resulting from the deposition of Research Article 131 I, 132 I, 133 I, 134 I, and 135 I on the ground, vegetation, milk, and meat in the event of a hypothetical accident involving a TRIGA research reactor. The study found that 131 I contributes the most to the dose in vegetation compared to all other radionuclides.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the airborne fraction of these isotopes remaining to be released into the atmosphere from the 3MW(t) research reactor TRIGA Mark-II, which will be operate for 10 days. Our results were compared with some findings from the bibliography [8][9]. To elaborate on this work, we need to specify certain parameters in advance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation